Effect of Addition of Spent Coffee Grounds Oil On the Performance of Diesel Engine - Richard Anthonius Wongso Santoso; Fandi Dwiputra Suprianto; Willyanto Anggono (Mechanova, 2017)
Energy demand has continued to rise since the industrial revolution and continues to increase as industry develops and population growth. About 80% of the world's energy is supplied by fossil fuels, which will be exhausted by the years to come. To solve this problem, the industries use waste vegetable oils and animal fats to produce biodiesel. Some also use non-edible waste as a biodiesel producer. Biodiesel can be produced from spent coffee grounds. The oil extracting is carried out using soxhlet and n-hexane which is purified using a rotary evaporator in the next move. Methyl esters are taken through the transesterification process. Methyl esters are mixed with diesel fuel. Then a characteristic test was conducted at Pertamina's Laboratory and performance test on ISUZU 4JA-1 OHV diesel engine using water brake dynamometer. The results of characteristics test of B10, B15, and B20 meet the requirements of the Directorate General of Oil and Gas Indonesia Number 28K/10/DJM.T/2016. The results of the sequential performance test for B10, B15, B20 produce peak power at 2000 RPM with values of 38.74 Hp, 40.35 Hp, 39.14 Hp, peak torque at 1800 RPM of 146.56 Nm, 153.37 Nm, 150.94 Nm, sfc 0.20 kg/Hp.h, 0.21 kg/Hp.h, 0.21 kg/Hp.h, and thermal efficiency 32.60%, 29.91%, 30.87%.